Pembelajaran Tahfidz Al-Qur’an: Studi Komparasi di SMP Plus Babussalam Bandung dan Pondok Pesantren Tahfidz Yatim Dhuafa Al-Afiyah Bandung - Ayu Desrani; Ratna Juami (Jurnal test, 2022)
This study aims to determine the comparison of the two institutions that carry out online tahfidzul Qur'an learning, namely Junior High School Plus Babussalam Bandung and offline learning, namely Tahfidz Yatim Dhuafa Al-Afiyah Islamic Boarding School, Bandung. Data collection techniques through observation, interviews and documentation were limited to informants with data analysis techniques including data triangulation with the stages of data collection, data reduction, data presentation and conclusion drawing. The findings of this study indicate that there is a very significant difference in the implementation of learning between the two institutions. Junior High School Plus Babussalam carries out online learning using the classical method, namely the teacher sends voice notes via whatsapp and students follow it and also collects memorization using whatsapp. The evaluation was carried out offline with less effective results, namely the student's interest in memorizing was reduced so that there was a decrease in memorization. While the Tahfidz Yatim Dhuafa Islamic Boarding School continues to do offline learning using the Pakistani method, namely by collecting new memorization to the teacher along with old memorization. So that students are required to keep the previous memorization in order to improve the quality of memorization. This method is effective to use, but it is quite heavy because students are required to repeat and add memorization simultaneously.